STRATEGI PENGEMBANGAN OBJEK WISATA PANTAI PELAWAN, TANJUNG BALAI KARIMUN SEBAGAI KAWASAN STRATEGIS PARIWISATA BERKELANJUTAN - Hari Iskandar (Kepariwisataan: Jurnal Ilmiah, 2021)
This study aims to determine the extent to which development strategies have been implemented and in order to determine the inhibiting factors in developing Pelawan beach tourism objects for sustainable tourism areas in Tanjung Balai Karimun. This study uses a descriptive approach with qualitative research methods, then analysis using SWOT (Strength, Weakness, Opportunity and Threath), IFAS and EFAS matrices. The results of this study can be concluded that based on the SWOT matrix with internal IFAS factors and external factors EFAS has strengths with a score (0.900), weaknesses with a score (0.885), opportunities with a score (0.915), and threats with a score (0.843). The total strengths and weaknesses are (1,786), the total score of opportunities and threats is (1,758). While the results of the SWOT diagram matrix, it can be concluded that the difference between the internal factors of strength and weakness, the X axis of the horizontal line with a value (0.15) and the difference between the external factors of opportunity and threat, namely the Y axis in the form of a vertical line with a value of (0.072). It can be concluded that Pelawan beach tourism object is included in Quadrant I, namely a progressive strategy. The position of Pelawan beach tourism object is in an advantageous position because this tourist attraction has the opportunity to increase the availability of facilities and infrastructure as an initial reference for tourism development and take advantage of the strengths of Pelawan beach attractions.Suggestions from the results of this study are the IFAS and EFAS factors, namely the availability of facilities and infrastructure as an initial reference for tourism development, so that it needs to be rebuilt and increase the ability of human resources so that the strategies developed are more focused and better.Keywords: Development Strategy; Sustainable Tourism; SWOT Analysis; IFAS, EFAS